Gum health and quality of life-subjective experiences from across the gum health-disease continuum in adults - Tom Broomhead; B Gibson; CR Parkinson; MV Vettore; SR Baker (BMC, 2022)
Abstract Background There has been a lack of qualitative work investigating the effects of the wide range of gum-related symptoms, and the perceived everyday impacts associated with these including on quality of life. While periodontal disease has been shown to have significant effects on quality of life, fewer studies have researched the perceived impacts of gingivitis and symptoms from across the entire gum health-disease continuum, despite evidence that these can also negatively affect quality of life. The aim of this study was to investigate perceived everyday impacts and explore the subjective experiences of adults with a variety of symptoms from across the self-reported gum health-disease continuum, and how these may affect quality of life. Methods Participants were recruited at a large UK University using purposive sampling, for self-reported symptoms ranging from mild gingivitis to severe periodontal disease. Semi-structured interviews gathered details on symptom history, changes occurring over time and associated beliefs, as well as perceived impacts on everyday life, and links between these experiences and identity. Interviews were analysed using framework analysis based on the Wilson and Cleary health-related quality of life model. Results Twenty-seven participants were recruited − 15 with symptoms of gingivitis, 12 with more severe periodontal symptoms. Prominent themes included description of symptoms, changes in daily life, social impacts, psychological impacts, identity, and overall impacts and quality of life. Differences were noted in severity, extent and frequency of symptoms and participant experiences, with greater perceived impacts often felt by those with periodontal disease. However, participants from across the gum health-disease continuum often expressed similar experiences and concerns. Conclusion Findings demonstrate the range of experiences from participants with a variety of gum-related symptoms; notably, gingivitis was reported to have a range of perceived impacts on quality of life alongside those reported by periodontal disease sufferers. Future work should look to include symptoms from across the entire gum health-disease continuum when considering quality of life, as well as considering a more patient-centred approach which could be valuable in both clinical and research settings.